2019
DOI: 10.1038/s41598-019-39163-9
|View full text |Cite
|
Sign up to set email alerts
|

Host plant and population source drive diversity of microbial gut communities in two polyphagous insects

Abstract: Symbioses between insects and microbes are ubiquitous, but vary greatly in terms of function, transmission mechanism, and location in the insect. Lepidoptera (butterflies and moths) are one of the largest and most economically important insect orders; yet, in many cases, the ecology and functions of their gut microbiomes are unresolved. We used high-throughput sequencing to determine factors that influence gut microbiomes of field-collected fall armyworm ( Spodoptera frugiperda ) and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(161 citation statements)
references
References 68 publications
10
147
3
1
Order By: Relevance
“…Our observations are somewhat contrasting with other systems in which nutritionally acquired metabolites of the host plant have been observed to strongly shape the animal gut communities (Koropatkin et al, 2012;Etxeberria et al, 2013;Lu et al, 2014;Xu et al, 2016). Our results also contrast several other studies in insects that have highlighted the importance of host plant in shaping the gut microbiota community (Broderick et al, 2004;Xiang et al, 2006;Pinto-Tomás et al, 2011;Gayatri Priya et al, 2012;Mason and Raffa, 2014;Berman et al, 2018;Jones et al, 2019), including a study of actively feeding late instar stage of M. cinxia (Ruokolainen et al, 2016). The microbiota of actively feeding individuals are evidently affected by the plant material that they feed on, which can lead to rapid and reversible changes in the microbiota community depending on the organic matter, defensive metabolites.…”
Section: Effects Of Host Plant's Microbiota and Metabolite Compositioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our observations are somewhat contrasting with other systems in which nutritionally acquired metabolites of the host plant have been observed to strongly shape the animal gut communities (Koropatkin et al, 2012;Etxeberria et al, 2013;Lu et al, 2014;Xu et al, 2016). Our results also contrast several other studies in insects that have highlighted the importance of host plant in shaping the gut microbiota community (Broderick et al, 2004;Xiang et al, 2006;Pinto-Tomás et al, 2011;Gayatri Priya et al, 2012;Mason and Raffa, 2014;Berman et al, 2018;Jones et al, 2019), including a study of actively feeding late instar stage of M. cinxia (Ruokolainen et al, 2016). The microbiota of actively feeding individuals are evidently affected by the plant material that they feed on, which can lead to rapid and reversible changes in the microbiota community depending on the organic matter, defensive metabolites.…”
Section: Effects Of Host Plant's Microbiota and Metabolite Compositioncontrasting
confidence: 99%
“…Our observations are somewhat contrasting with other systems in which nutritionally acquired metabolites of the host plant have been observed to strongly shape the animal gut communities (Koropatkin et al ., ; Etxeberria et al ., ; Lu et al ., ; Xu et al ., ). Our results also contrast several other studies in insects that have highlighted the importance of host plant in shaping the gut microbiota community (Broderick et al ., ; Xiang et al ., ; Pinto‐Tomás et al ., ; Gayatri Priya et al ., ; Mason and Raffa, ; Berman et al ., ; Jones et al ., ), including a study of actively feeding late instar stage of M . cinxia (Ruokolainen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the distribution of ASVs among phyla and families of bacteria, the alimentary canal bacteria of T. ni larvae feeding on collards appeared similar to other lepidopteran species (Jones et al, ; Paniagua Voirol, Frago, Kaltenpoth, Hilker, & Fatouros, ). The two most abundant ASVs from the midgut and other organs, apparently belong to the genera Cloacibacterium and Diaphorobacter , members of which have been previously reported from insect gut microbiomes (Montagna et al, ; Ravenscraft, Kish, Peay, & Boggs, ).…”
Section: Resultsmentioning
confidence: 76%
“…Various studies have shown that abundant microorganisms, particularly bacteria, persist in the larval gut across a range of Lepidoptera species . However, the majority of these studies have focused on structural differences in the bacterial community, with few examining functional variability in bacterial communities across different species within Lepidoptera . For example, Heliconius butterflies have a conserved microbiota dominated by Bacillus , Enterococcus and Enterobacteriaceae, whereas abundant Carnobacterium are observed in the spring webworm and diamondback moth microbiotas …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] However, the majority of these studies have focused on structural differences in the bacterial community, with few examining functional variability in bacterial communities across different species within Lepidoptera. 20,21 For example, Heliconius butterflies have a conserved microbiota dominated by Bacillus, Enterococcus and Enterobacteriaceae, 22 whereas abundant Carnobacterium are observed in the spring webworm and diamondback moth microbiotas. 23 As a result, we currently do not know how the metabolic capacity of bacterial communities varies as a function of host phylogeny and whether there are predictable patterns driven by the host phenotype within Lepidoptera.…”
Section: Introductionmentioning
confidence: 99%